2009
DOI: 10.1017/s0022215109005623
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of nasopharyngeal carcinoma in Chinese immigrants, compared with Chinese in China and South East Asia: review

Abstract: This review found a decreasing trend in the incidence of nasopharyngeal carcinoma in Chinese migrants living in countries with a low risk of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…NPC occurs particularly frequent in China and Southeast Asia, with an annual incidence rate of about >20 per 100,000 in endemic areas (Yu et al, 2002;Bray et al, 2005;Chang et al, 2006). Descendants of Chinese who emigrated to Western countries have lower NPC incident rates than do Chinese in Asia, but their rates remain higher than those of White populations in Western countries (Buell et al, 1974;Yu et al, 2009). Globally, NPC accounts for about 80,000 new cases and 50,000 deaths annually (Bray et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…NPC occurs particularly frequent in China and Southeast Asia, with an annual incidence rate of about >20 per 100,000 in endemic areas (Yu et al, 2002;Bray et al, 2005;Chang et al, 2006). Descendants of Chinese who emigrated to Western countries have lower NPC incident rates than do Chinese in Asia, but their rates remain higher than those of White populations in Western countries (Buell et al, 1974;Yu et al, 2009). Globally, NPC accounts for about 80,000 new cases and 50,000 deaths annually (Bray et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In NPC epidemic regions, the incidence rate is about 20-30/100,000 general population. The etiological factors associated with the geographic and ethnic pattern of NPC remain unclear.…”
mentioning
confidence: 99%
“…Environmental factors are important as migrant studies have shown that the rates decline to intermediate rates between the countries of origin and countries of residence. (Yu and Hussain 2009;Mousavi et al, 2010). Low economic social status, an indirect indicator to exposures of the risk factors has also been reported to be associated with NPC.…”
Section: Discussionmentioning
confidence: 99%